Associations among sedentary and active behaviours, body fat and appetite dysregulation: investigating the myth of physical inactivity and obesity. Issue 21 (4th April 2016) - Myers, Anna; Gibbons, Catherine; Finlayson, Graham; Blundell, John
Abstract : Background: There is considerable disagreement about the association between free-living physical activity (PA) and sedentary behaviour and obesity. Moreover studies frequently do not include measures that could mediate between PA and adiposity. The present study used a validated instrument for continuous tracking of sedentary and active behaviours as part of habitual daily living, together with measures of energy expenditure, body composition and appetite dysregulation. This cross-sectional study tested the relationship between inactivity and obesity. Methods: 71 participants (81.7% women) aged 37.4 years (±14) with a body mass index of 29.9 kg/m 2 (±5.2) were continuously monitored for 6–7 days to track free-living PA (light 1.5–3 metabolic equivalents (METs), moderate 3–6 METs and vigorous >6 METs) and sedentary behaviour (<1.5 METs) with the SenseWear Armband. Additional measures included body composition, waist circumference, cardiovascular fitness, total and resting energy expenditure, and various health markers. Appetite control was assessed by validated eating behaviour questionnaires. Results: Sedentary behaviour (11.06±1.72 h/day) was positively correlated with fat mass (r=0.50, p<0.001) and waist circumference (r=−0.65, p<0.001). Moderate-to-vigorous PA was negatively associated with fat mass (r=−0.72, p<0.001) and remained significantly correlated with adiposity after controlling for sedentary behaviour. Activity energy expenditure was positively associated with the level of PA and negatively associated with fat mass. Disinhibition and binge eating behaviours were positively associated with fat mass (r=0.58 and 0.47, respectively, p<0.001). Conclusions: This study demonstrated clear associations among objective measures of PA (and sedentary behaviour), energy expenditure, adiposity and appetite control. The data indicate strong links between physical inactivity and obesity. This relationship is likely to be bidirectional.